Harmful and Useful Thrips in Medicago sativa L. - Nikolova Ivelina (Agriculture)
Spring alfalfa sowing was grown under non-irrigated conditions in the Experimental field of the Institute of Forage Crops, Pleven, Bulgaria. From 2018 to 2021, forage harvesting was performed at the flowering stage in four regrowth periods during the growing season. Sweeping with an entomological net was used. Canonical relationship analysis revealed that the population density of Thysanoptera phytophagous and predator species was positively related to the temperature while humidity and rainfall negatively affected the thrips numbers. Thirteen species from three families, as well as eight genera of Thysanoptera, were identified. The family Thripidae was the most diverse, with a participation rate of 53.17%, represented by five genera and ten species. The Aeolothripidae family had a participation rate of 44.0% with two species. Harmful species comprised 55.16% of the Thysanoptera species, while useful species accounted for 44.0%. The dominant species, Thrips tabaci Lindeman, 1889, made up 37.38% of the population, followed by the subdominant species T. atratus Haliday (1836) at 9.66%. The dominant species Aeolothrips intermedius Bagnall, 1934, accounted for 43.81% of the population density and mostly represented predatory thrips. Throughout the alfalfa growing season, T. tabaci was present, with the highest density observed during the second regrowth from late May to late June. The peak density occurred in the first ten days of June, during the button and early flowering stages. The population dynamics of A. intermedius corresponded with those of T. tabaci, indicating its significant role as a biological agent in alfalfa.